Finite Horizon Holdup and How to Cross the River - Simon Martin; Karl Schlag (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
When should one pay for delivery of a good if there are no institutions? We suggest to break up the transaction into many small rounds of investment and payment. We show that the efficient investment can be implemented in an epsilon-subgame perfect equilibrium for any given epsilon if the invest technology is concave and there are sufficiently many rounds of investment. This shows that the holdup problem that emerges from backwards induction in a finite horizon is not robust.
Keywords: D23; C72; L14; 330